2022
DOI: 10.3389/fnhum.2021.755017
|View full text |Cite
|
Sign up to set email alerts
|

Altered Structural and Functional MRI Connectivity in Type 2 Diabetes Mellitus Related Cognitive Impairment: A Review

Abstract: Type 2 diabetes mellitus (T2DM) is associated with cognitive impairment in many domains. There are several pieces of evidence that changes in neuronal neuropathies and metabolism have been observed in T2DM. Structural and functional MRI shows that abnormal connections and synchronization occur in T2DM brain circuits and related networks. Neuroplasticity and energy metabolism appear to be principal effector systems, which may be related to amyloid beta (Aβ) deposition, although there is no unified explanation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 176 publications
1
5
0
Order By: Relevance
“…In addition, pED, owing predominantly to psychological factors including anxiety, depression, and introversion, was found to be more vulnerable to structural and functional changes in the prefrontal regions ( 26 , 27 , 38 ). Therefore, our findings were in agreement with the central neural mechanisms of pED and DM in previous neuroimaging studies ( 11 , 38 , 50 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, pED, owing predominantly to psychological factors including anxiety, depression, and introversion, was found to be more vulnerable to structural and functional changes in the prefrontal regions ( 26 , 27 , 38 ). Therefore, our findings were in agreement with the central neural mechanisms of pED and DM in previous neuroimaging studies ( 11 , 38 , 50 ).…”
Section: Discussionsupporting
confidence: 93%
“…An epidemiological study suggested that the prevalence of diabetes was increasing rapidly, and the prevalence of erectile dysfunction (ED) among diabetic patients varied from 35 to 90% ( 10 ). Compared with the general population, patients with T2DM have a higher risk for cognitive decline, which is one of the central nervous system complications associated with abnormalities of brain function and structure ( 11 13 ). In addition, T2DM patients are at higher risk of developing male sexual dysfunction, including ED and retrograde ejaculation, which are two common peripheral microvascular and neurological complications associated with oxidative stress-induced penile vascular endothelial cell injury and peripheral neuropathy ( 14 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological screening tests are easily performed in most clinics or hospitals, but the fact that the neuropsychological data were difficult to be interpreted has increased the necessity of medical images, artificial intelligence, and even a combination of them. In the field of medical image, several Cognitive dysfunction biomarkers have been studied including the brain metabolic change derived from fluorodeoxyglucose positron emission tomography (FDG-PET) ( Yuan et al, 2009 ; Pardo et al, 2010 ; Newberg et al, 2022 ), and the structural or functional change in the brain measured by MRI ( van Harten et al, 2007 ; Belfort-Deaguiar et al, 2014 ; Lei et al, 2021 ). In recent years, with the development of MRI scanner and its increasingly enhanced data processing function, the level of analysis has been moving from assessment of brain structure and morphology such as volume and general atrophy to more detailed and in-depth analysis of white matter tracts, using diffusion tensor imaging (DTI), a newer method.…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rs-fMRI) is a promising approach with which to studying the brain-related pathophysiology of T2DM ( Chau et al, 2021 ; Lei et al, 2022 ). Functional connectivity (FC) is an effective method to explore impaired frontostriatal circuits ( Di Martino et al, 2008 ; Kelly et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%